Proportional responsibility versus individual responsibility for healthy eating: a complex systems analysis. (November 2017) - Savona, Natalie; Thompson, Claire; Smith, Dianna; Cummins, Steven
Abstract: Background: Most public health interventions on diet place responsibility on individuals (eg, to use information to make healthy food choices); on a population level, such strategies are ineffectual. Here we report on research into perceptions of responsibility for healthy eating, using a complex systems framework. The aim of the research was to provide insights into the impact of the food system—rather than single variables—on the public's diet. Methods: The data gathered comprised eight industry and government documents, from the baseline of Foresight's 2007 obesity report to the 2011 Public Health Responsibility Deal, including corporate signatories to the latter; eight focus groups with members of the public; and 18 interviews with representatives from sectors responsible for creating the food environment (ie, food industry, government, and non-governmental organisation). Responsibility for healthy eating was explored using Foucauldian discourse analysis; this incorporated consideration of the properties of complex systems, such as the inter-relatedness of actors and the fluid, non-linearity of interactions, interventions, and outcomes. Findings: The data show that despite claims of shared responsibility for dietary behaviour, government and corporations use rhetoric and measures that deflect regulations or action for which they are responsible that could help improve the population's diet, such as food reformulation or advertising restrictions. They also favour downstream interventions, such as food labelling, that place high agency on individuals, rather than more effective, upstream, regulatory or fiscal strategies. Interpretation: Problematising responsibility highlights how the onus is mostly on individuals for healthy food choices even though individuals themselves have the least power over key drivers of those choices: taste, cost, convenience, promotions. A complex systems approach helps explain how the mismatch between power and responsibility contributes to a food system in which many people consume diets detrimental to their health. Proportional responsibility offers a counterfactual framework to the dominant policies that attribute ultimate responsibility for eating healthily to individuals, given that they have proportionally less influence over the determinants of their food choices than do government and the food industry. This concept could be explored as a potential framework for examining whether policies attribute responsibility for health-promoting behaviour proportionally to a group's capacity to act. Funding: This research was funded by Queen Mary University of London and the London School of Hygiene & Tropical Medicine as a PhD scholarship (to NS).